'With these exhibits many interesting things can be learned about past times': Playmobil's History Class – representations, reflections and expectations. Issue 2 (20th October 2020) - Barsch, Sebastian; Mathis, Christian
Abstract : page_151 other In 2018, the toy manufacturer Playmobil launched a 'History Class' as an addition to its 'Furnished School Building'. The materiality of this toy, and the selection of teaching media represented in coloured plastic (a blackboard with timeline, magnifying glass, parchment roll, stone axe, posters and other sources), convey an idea of history education based on hands-on learning, a variety of methods, original encounters and work with historical sources. This paper presents results of an international research project in which 12 children in Germany and Switzerland were interviewed with the help of this toy as a stimulus. The aim was to find out to what extent children are able to deconstruct the toy as a historical-cultural product. In addition, the interviews were intended to grasp the children's views on the ideal teaching of history. The data are evaluated using grounded theory methodology. The results show that the pupils express clear wishes as to how history teaching should be structured. A critical distance to the toy was not taken.